Parenting Styles and Academic Achievement of Rural Students at SMPN 23 Bengkulu Tengah: A Qualitative Descriptive Study - Tias Siswanti; Adi Asmara (Assyfa Journal of Islamic Studies, 2026)
This study examines the relationship between parenting styles and the academic achievement of students at SMPN 23 Bengkulu Tengah, Indonesia, using a descriptive qualitative approach. The research aims to understand how parenting dynamics in rural settings contribute to student academic outcomes and to identify key inhibiting factors. Data were collected through participatory observation, in-depth interviews with parents and teachers, and systematic documentation of student academic records. Thematic analysis following the Miles, Huberman, and Saldaña (2020) framework revealed that parental involvement remains predominantly passive, limited to fulfilling tangible needs such as uniforms and stationery, while emotional and educational support—homework accompaniment, motivation, and self-confidence building—is critically lacking. Three primary inhibiting factors were identified: severe economic pressure that exhausts parental time and energy, low parental education literacy leading to academic self-doubt and abdication of responsibility to schools, and deep-rooted institutional misconceptions about the sole responsibility of schools for children's character and academic development. Despite these constraints, when present, emotional involvement showed a significant positive effect on student motivation. The study concludes that academic success in rural areas is more determined by the quality of parenting and intensity of parental involvement than by economic conditions alone. Sustainable parenting programs and consistent school budget transparency are recommended as key strategies to build trust and foster a synergistic school-family partnership that supports holistic student development.